Prevalence of Brain Magnetic Resonance Imaging Diagnoses and Correlation With Signalment and Presenting Complaint in Dogs - Walsh, Nicholas; Carney, Patrick C.; Streu, Shayna; Thompson, Margret; Johnson, Philippa J. (Frontiers in Veterinary Science, 2021)
Since magnetic resonance imaging (MRI) was introduced, it has become increasingly available and technologically improved. Studies have documented the prevalence of specific pathologies, however no previous veterinary studies have investigated the prevalence and distribution of pathology across all MRIs performed at a single institution. The present study aimed to evaluate the prevalence of MRI-diagnosed brain lesions and correlate these to patient signalment and presenting complaint. Archived MRI brain scans from 805 dogs were reviewed retrospectively. One board-certified veterinary radiologist at the institution retrospectively evaluated all reports to determine the most clinically pertinent imaging diagnosis for each case. Breed, age, and presenting complaint were obtained from the medical record for each patient. The most common imaging diagnoses across all dogs reviewed were no significant findings (35.16%), asymmetric encephalopathy or meningoencephalopathy (19.75%), and extra-axial intracranial mass (11.18%). Age of dogs differed by diagnosis (p<0.0001), with the median age of dogs diagnosed with a brain mass being greater than that of dogs with no significant findings and dogs with asymmetric encephalopathy or meningoencephalopathy (both p<0.0083). In dogs presenting with seizures, the odds of a brain mass increased with each additional year of age (p<0.0001, odds ratio 1.26 [95% CI 1.16-1.37]), whereas the odds of no significant finding (p<0.0001, OR 0.87 [0.82-0.93]) decreased. Our findings provide overview information on the types of disease observed in the clinical population and allow us to detect correlations between imaging diagnoses, presenting complaints, and signalment.